Rivoluzioni: una tradizione europea? - Benigno, Francesco (Studi Politici, 2023)
Today, the concept of revolution is no longer that unquestioned cast modelled on the French Revolution as the bearer of the new world and which arranged the conflict along a differentiated value scale in which revolutions stood at the top, followed at lower levels by incomplete and disrupted, or failed, revolts or insurrections, thought of at most as aborted revolutions. Overcoming the ‘modern’ or classical conception of revolution means conceiving it not as the almost mechanical effect of the predetermined action of professional revolutionaries, but instead as the outcome of a political crisis in which contradictory drives and tendencies manifest themselves. In this view, it is not so much the revolutionaries who make the revolution as the revolution ‘makes’ the revolutionaries. It is, in short, a question of repositioning revolutions, which are no longer to be thought of as the ineluctable stages of assured progress, of the future world to come, and of the first absolute and then modern state, but instead as part of the political struggle, markers of the path to building European freedom, moments of the creation of decisive intellectual traditions that cannot be ignored.